2012
DOI: 10.4174/jkss.2012.83.5.321
|View full text |Cite
|
Sign up to set email alerts
|

Sarcomatoid carcinoma of the small intestine: a rare and highly aggressive tumor

Abstract: Sarcomatoid carcinoma of the small intestine is an extremely rare malignant neoplasm that usually has a poor prognosis. We report a case of sarcomatoid carcinoma arising in the small intestine in a 62-year-old man who was hospitalized for abdominal pain. Computed tomography revealed wall thickening of the small intestine. The resected specimen showed a gray-whitish solid mass with hemorrhage and necrosis. Microscopically, the tumor was composed of pleomorphic spindle and discohesive polygonal cells with freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 10 publications
3
22
0
Order By: Relevance
“…The average size is about 7.5 cm with a range of 3–16 cm 8. The use of immunohistochemical markers helps in a wide range of differential diagnoses which include epithelioid angiosarcoma, leiomyosarcoma, epithelioid MPNST, GIST, lymphoma and melanoma 3. Lymphovascular invasions are found in 55% of the cases, similar to our case 8…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The average size is about 7.5 cm with a range of 3–16 cm 8. The use of immunohistochemical markers helps in a wide range of differential diagnoses which include epithelioid angiosarcoma, leiomyosarcoma, epithelioid MPNST, GIST, lymphoma and melanoma 3. Lymphovascular invasions are found in 55% of the cases, similar to our case 8…”
Section: Discussionsupporting
confidence: 80%
“…Patients usually have different, non-specific symptoms including: abdominal pain, intestinal obstruction, as in our case presentation, palpable abdominal mass, nausea, vomiting, weight loss, GI bleeding and anaemia 3 7. Zhang et al noted that anaemia and abdominal pain have been the two most common presentations 8.…”
Section: Discussionmentioning
confidence: 73%
“…Symmetric or asymmetric wall thickening with fold effacement was noted in three cases (3,4,7). CT failed to detect the lesion in three cases (6,8,9).…”
Section: Index Termsmentioning
confidence: 92%
“…Further studies for comparing CT finding of biphasic and monophasic sarcomatoid carcinoma will be necessary. Small bowel series was done together with the CT in several cases (6)(7)(8)10). The study revealed the intraluminal polypoid mass (6,8,10), although CT failed to detect the lesion (6,8) or mimicked the pancreatic cancer (10).…”
Section: Index Termsmentioning
confidence: 99%
“…(14) In summary, sarcomatoid carcinoma is a biphasic malignant neoplasm with carcinomatous and sarcomatous components. Thus, it has a high degree of malignancy and a poor prognosis, (15) and the risk of local recurrence or distant metastases is also very high. The main radiographic and CT appearance of mandibular sarcomatoid carcinoma is diffuse, irregular osteolytic bone destruction with a soft tissue mass, generally without bone sclerosis or expansion.…”
Section: Discussionmentioning
confidence: 99%